2018
DOI: 10.1186/s13046-018-0963-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer associated with obesity and diabetes: an alternative approach for its targeting

Abstract: BackgroundPancreatic cancer (PC) is among foremost causes of cancer related deaths worldwide due to generic symptoms, lack of effective screening strategies and resistance to chemo- and radiotherapies. The risk factors associated with PC include several metabolic disorders such as obesity, insulin resistance and type 2 diabetes mellitus (T2DM). Studies have shown that obesity and T2DM are associated with PC pathogenesis; however, their role in PC initiation and development remains obscure.Main bodySeveral bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 183 publications
(177 reference statements)
0
69
0
2
Order By: Relevance
“…Overweight, that frequently characterized type 2 diabetes, could play a crucial role in carcinogenesis [62,63]. Adipose tissue is a complex endocrine organ able to secrete a variety of bioactive molecules (cytokines, free fatty acids, TNFalfa, plasminogen activator inhibitor-1 (PAI-1) and adiponectin) which may lead malignant transformation and progression [64]. Further, adipose tissue microenvironment promotes concomitant systemic endocrine alterations (obesity-related insulin resistance, hyperinsulinemia, sustained hyperglycemia) which, in turn, are involved in cancer development [65].…”
Section: Long-standing Diabetes Several Mechanisms Have Been Suggestementioning
confidence: 99%
“…Overweight, that frequently characterized type 2 diabetes, could play a crucial role in carcinogenesis [62,63]. Adipose tissue is a complex endocrine organ able to secrete a variety of bioactive molecules (cytokines, free fatty acids, TNFalfa, plasminogen activator inhibitor-1 (PAI-1) and adiponectin) which may lead malignant transformation and progression [64]. Further, adipose tissue microenvironment promotes concomitant systemic endocrine alterations (obesity-related insulin resistance, hyperinsulinemia, sustained hyperglycemia) which, in turn, are involved in cancer development [65].…”
Section: Long-standing Diabetes Several Mechanisms Have Been Suggestementioning
confidence: 99%
“… 1 , 2 Some studies have shown that smoking, obesity, diabetes and pancreatitis are risk factors for PC, and approximately 10% of PC patients have a family background. 3 - 6 The prevalence of obesity is high in Chinese population. 7 - 9 Delineating obesity could be a beneficial strategy to combat PC.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of childhood obesity remains increasing in recent decades, which is alarming because it is also associated with health consequences such as metabolic syndrome, diabetes, cardiovascular diseases and even many types of cancers in adulthood 1 2. Once a child is obese that is more likely to remain during adulthood 3–5.…”
Section: Introductionmentioning
confidence: 99%